PUBLIC DEMAND FOR IMPROVED URBAN WATER SUPPLY SERVICES IN MULTAN:A CRITICAL REVIEW PAPER - Maimoona Arshad; Mehwish Kanwal; Sundas Khabir (Dinasti International Journal of Education Management And Social Science, 2020)
Governments in developing countries face financial constraints to ensure supply of clean drinking water. They may benefit from increasing water charges for those who are be willing to pay little extra in lieu of their demand for improvement in water quality and service. To check the plausibility of this proposal, we investigated drinking water supply and quality, and well- off consumers demand for improved service delivery in Shah-Rukun-e-alam and Mumtazabad towns in Multan city of Pakistan. Qualitative data obtained through a questionnaire survey was analyzed using descriptive and regression techniques. Qualitative information obtained through semi structured interviews was helpful in designing survey questionnaire and to elaborate quantitative results. Results reveal that the respondents accord high importance to the provision of safe drinking water than to other daily household needs. The demand for improvement in water supply parameters exceeds the demand for improvements in water quality parameters, with the reliable supply being the most demanded improvement. Majority realize the government’s budget constraints in improving service delivery. Most respondents would pay PKR 100 in addition to what they are paying now. Their willingness to pay (WTP) this amount correlates with their awareness on water and health nexus, and depends household income, number of children under 14 years age and awareness of actual water quality tested through laboratory. Besides recommending raise of water charges by PKR 100 per month per household in both towns, the service quality improvement may consider interventions such as mobile water testing laboratory and awareness campaigns motivate citizens to pay for safe drinking water.